Whole-genome/exome analysis of circulating tumor DNA and comparison to tumor genomics from patients with heavily pre-treated ovarian cancer: subset analysis of the PERMED-01 trial - Sabatier, Renaud; Garnier, Séverine; Guille, Arnaud; Carbuccia, Nadine; Pakradouni, Jihane; Adelaide, José; Provansal, Magali; Cappiello, Maria; Rousseau, Frédérique; Chaffanet, Max; Birnbaum, Daniel; Mamessier, Emilie; et al. (Frontiers in Oncology, 2022)
Introduction. The poor prognosis of ovarian carcinoma is due to advanced stage at diagnosis, a high risk of relapse after first-line therapies, and the lack of efficient treatments in the recurrence setting. Circulating tumor DNA (ctDNA) analysis is a promising tool to assess treatment resistant ovarian cancer (OvC) and may avoid iterative tissue biopsies. We aimed to evaluate the genomic profile of recurrent heavily pre-treated OvC. Methods. We performed tumor panel-based sequencing as well as low-coverage whole-genome sequencing (LC-WGS) of tumor and plasma collected in patients with ovarian cancer included in the PERMED-01 trial. Whole-exome sequencing (WES) data of plasma samples were also analyzed and compared to mutation and copy number alterations (CNAs) tumor profiles. The prognostic value (progression-free survival, PFS) of these alterations was assessed in an exploratory analysis. Results. Tumor and plasma genomic analyses were done for 24 patients with heavily pretreated OvC (67% high-grade serous carcinoma (HGSC)). Tumor mutation burden was low (median 2.04 mutations/Mb) and the most frequent mutated gene was TP53 (94% of HGSC). Tumor CNAs were frequent with a median of 50% of genome altered. Plasma LC-WGS and WES detected ctDNA in 21/24 cases (88%) with a median tumor fraction of 12.7%. We observed a low correlation between plasma and tumor CNAs profiles. However, this correlation was significant in cases with the highest circulating tumor fraction. Plasma genome altered fraction and plasma mutation burden (p=0.011 and p=0.041, respectively, log-rank tests) were associated with PFS. Conclusions. Combination of LC-WGS and WES can detect ctDNA in most of pre-treated ovarian carcinoma. Some ctDNA characteristics, such as genome altered fraction and plasma mutation burden, showed prognostic value. ctDNA assessment with LC-WGS may be a promising and not expansive tool to evaluate disease evolution in this disease with high genomic instability.